2019
DOI: 10.1080/19490976.2019.1629236
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and consequences of gut commensal translocation in chronic diseases

Abstract: Humans and other mammalian hosts have evolved mechanisms to control the bacteria colonizing their mucosal barriers to prevent invasion. While the breach of barriers by bacteria typically leads to overt infection, increasing evidence supports a role for translocation of commensal bacteria across an impaired gut barrier to extraintestinal sites in the pathogenesis of autoimmune and other chronic, non-infectious diseases. Whether gut commensal translocation is a cause or consequence of the disease is incompletely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 83 publications
(146 reference statements)
1
64
0
1
Order By: Relevance
“…Although gut barrier disruption has not been reported to be a pre requisite for nonalcoholic steatohepatitis (NASH) development and belongs to the 'multiple hit' pathogenesis of disease progression [60], more recent observations in preclinical models have shown that disruption of epithelial and vascular barriers in the intestine were early events reported in NASH [61]. Gut-liver axis deterioration has also been described in patients with chronic liver diseases who develop sepsis and multiorgan failure [62,63]. Zhou et al in their recent retrospective cohort study of 191 patients reported that more than half of hospitalized patients developed sepsis as a common complication of SARS-CoV-2 infection [18].…”
Section: Discussionmentioning
confidence: 99%
“…Although gut barrier disruption has not been reported to be a pre requisite for nonalcoholic steatohepatitis (NASH) development and belongs to the 'multiple hit' pathogenesis of disease progression [60], more recent observations in preclinical models have shown that disruption of epithelial and vascular barriers in the intestine were early events reported in NASH [61]. Gut-liver axis deterioration has also been described in patients with chronic liver diseases who develop sepsis and multiorgan failure [62,63]. Zhou et al in their recent retrospective cohort study of 191 patients reported that more than half of hospitalized patients developed sepsis as a common complication of SARS-CoV-2 infection [18].…”
Section: Discussionmentioning
confidence: 99%
“…In the lamina propria, B cells may also switch into IgA in a T cell-independent way (21). The T cell-independent generation of SIgA by B cells may represent a mechanism to generate IgA expressing a wide repertoire of Ig genes, useful to face the thousands of different bacterial species of the microbiota (23,24,42), and to control host-microbiota mutualism, reducing the risk of bacterial translocation and immune activation (43)(44)(45). IgM memory B cells have been shown to home to the gut and to locally switch to IgA (21,46).…”
Section: Discussionmentioning
confidence: 99%
“…The role of the gut-liver axis in immune pathologies is highlighted by recent examples of breaches of the gut epithelial barrier leading to liver and systemic immune pathologies (reviewed in ref. 53 ). These include Enterococcus gallinarum translocating from the mouse small intestine to the MLNs, liver and, over time, the spleen, driving both organ-specific and systemic autoimmunity through various mechanisms 11 (fIg.…”
Section: Wwwnaturecom/nrmicromentioning
confidence: 99%